Impulsive Buying Behavior through the Attraction of Students Captivated with Kocs' Short Videos: Second-Hand Footwear Products - Nguyen Thi Phuong, Giang; Pham Thi Thanh , Truc; Le Thi Tam , Nhu; Nguyen Minh , Thu; Vo Thi Nguyet , Nhi; Thai Dong, Tan; Nguyen Binh Phuong, Duy (Asosiasi Ahli Administrasi Indonesia, 2024)
In the rapidly developing digital economy, Vietnamese students' consumption behavior is changing significantly, particularly with the rise of impulsive shopping influenced by short videos from Key Opinion Consumers (KOCs). Specifically, second-hand footwear products (used shoes) stand out as an item that is regularly introduced by KOCs and attracts great interest from students, leading to impulsive shopping decisions due to their affordability and uniqueness. This study investigates the impact of KOCs (Key Opinion Consumers) on the impulsive shopping behavior of Vietnamese students within the digital economy's evolving landscape. It analyzes how KOCs' short video content influences unplanned purchase decisions, utilizing a mixed-method approach. Initially, semi-structured interviews with 20-30 students explored their perceptions of KOCs and shopping behaviors, informing a subsequent quantitative survey conducted with 524 students in Ho Chi Minh City. After data filtering, 512 responses were analyzed using the PLS-SEM structural model in SMARTPLS-4 software. Findings reveal that factors such as product information, brand recognition, KOCs' appeal, and virality significantly influence impulsive buying behavior, mediated by the attractiveness of short videos. Additional influences include promotions, mood, instant feel, and affordability. This research offers valuable insights into youth consumer behavior in the digital age and highlights critical issues regarding financial management and influencer marketing effectiveness in Vietnam.